Project procurement method : the conflicts in construction projects procured under design and build method - Mai Ling, Teon (2014)
Design and build procurement method is one of the procurement methods where the contractor is responsible to carry out both the design and construction work of the project. Design and build contract give convenience to the client by combining project cost, schedule, design and quality into one single point of responsibility. Even though, design and build contract give many benefits to contractor and client but there are contractors and clients who still feel less excited with the benefits offered. The number of projects procured under design and build method are also decreasing in recent years. Therefore, this research purpose is to identify the conflicts in design and build construction project and propose the solution to overcome the conflicts in design and build contract. A research questionnaire was designed and distributed to 92 grade 7 contractors in Pahang state. The data obtained from respondents were analyzed using mean value analysis. The result of the survey indicated that five mostly occurred conflicts in design and build projects are variation order, delay in work activities, client delay (lack of payment), client lack interaction with contractor and time overrun or project delay. By referring to the literature review, contract form (Standard Form of Design and Build Contract – PWD Form DB (Rev.1/2010), Standard Form of Contract Be Used Where Drawings and Specifications Form Part of the Contract – PWD Form 203 (Rev. 1/2010) and Agreement and Conditions of PAM Contract 2006 with Quantities and interview with two experts from Perbadanan Kemajuan Negeri Pahang (PKNP) which are an engineer and an quantity surveyor, five solution flowcharts was proposed to overcome the five mostly occur conflicts in design and build projects. The result of this research will help the construction team, design team and client of design and build projects to systematically and effectively manage their conflicts and indirectly will help them in maintaining their good relationship. In the future study, it is proposed for the future researcher to increase the number of respondent by expanding the scope of study. When the scope of study is bigger, the researcher can know the various types of conflicts and propose a more accurate solution to overcome the conflicts